Design and implementation of interoperable high-efficiency bidirectional wireless power transfer systems for multiple vehicles - Zhang, Baokun; Deng, Junjun; Duan, Mengchen; Li, Chang; Zheng, Yi; Wang, Shuo; Dorrell, David (Elsevier Ltd, 2026)
The rapid growth of electric vehicle ownership and advancements in vehicle-to-grid (V2G) technologies have created an urgent demand for bidirectional charging–discharging interfaces. Wireless power transfer (WPT) technology, known for its convenience, safety, and flexibility, is a promising solution for energy transfer between vehicles and the grid. This paper presents the design and demonstration of a highly interoperable and high-efficiency bidirectional WPT system, addressing key challenges such as wide voltage output adaptation, multi-power level compatibility, and efficient operation over a broad power range. The front-end converter uses a power module combining a three-phase fully controlled rectifier and a cascaded buck converter to provide a wide DC voltage range. Modular activation technology ensures the grid interface operates efficiently under varying power demands. For the bidirectional inductive power transfer (BIPT) link, an integrated scheme for the resonant networks in the ground assembly (GA) with cross-frequency compatibility is proposed, and its performance is validated through calculations and simulations. A bidirectional power flow control strategy is implemented, with voltage regulation and operation mode switching as the main method. Experimental results demonstrate interoperability between the same grid-side equipment and different vehicle-side equipment rated at 6, 11, and 30 ​kW. Under specified operating conditions at the aligned position, the system achieves a grid-to-battery efficiency from 91.7% to 94.3%, and a battery-to-grid efficiency ranging from 89.5% to 93.5%.